Differences in situational efficiency between playing positions of elite U-19 soccer players - Marasovic, J.; Vukoša, L.; Rada, A. (Journal of Physical Education and Sport, 2025)
Purpose: There is a literature gap regarding positional differences between variables of situational efficiency during official matches in youth soccer. This study analyzed differences in offensive and defensive situational efficiency parameters based on playing positions among elite junior soccer players.